Systemic delivery of human GlyR IgG antibody induces GlyR internalization into motor neurons of brainstem and spinal cord with motor dysfunction in mice. (28th September 2020) - Carvajal‐González, A.; Jacobson, L.; Clover, L.; Wickremaratchi, M.; Shields, S.; Lang, B.; Vincent, A.
Abstract : Aims: Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a life‐threatening condition often associated with highly raised serum antibodies to glycine receptors (GlyRs); these bind to the surface of large neurons and interneurons in rodent brain and spinal cord sections and, in vitro, inhibit function and reduce surface expression of the GlyRs. The effects in vivo have not been reported. Methods: Purified plasma IgG from a GlyR antibody‐positive patient with PERM, and a healthy control (HC), was injected daily into the peritoneal cavity of mice for 12 days; lipopolysaccharide (LPS) to open the blood–brain barrier, was injected on days 3 and 8. Based on preliminary data, behavioural tests were only performed 48 h post‐LPS on days 5–7 and 10–12. Results: The GlyR IgG injected mice showed impaired ability on the rotarod from days 5 to 10 but this normalized by day 12. There were no other behavioural differences but, at termination (d13), the GlyR IgG‐injected mice had IgG deposits on the neurons that express GlyRs in the brainstem and spinal cord. The IgG was not only on the surface but also inside these large GlyR expressing neurons, which continued to express surface GlyR. Conclusions: Despite the partial clinical phenotype, not uncommon in passive transfer studies, the results suggest that the antibodies had accessed the GlyRs in relevant brain regions, led to antibody‐mediated internalization and increased GlyR synthesis, compatible with the temporary loss of function. Abstract : Purified IgG from a patient with progressive encephalopathy with rigidity and myoclonus (PERM) who had raised antibodies to the inhibitory glycine receptor was injected into mice together with lipopolysaccharide to open the blood–brain barrier. The mice developed a motor phenotype, indicated by falling off a rotating cylinder earlier than healthy IgG injected controls. At termination, these mice had deposits of IgG within the brainstem neurons which express glycine receptors, consistent with an antibody‐induced dysfunction of these neurons.